Evidence of waste electrical and electronic equipment (WEEE) relevant substances in polymeric food-contact articles sold on the European market - Puype, Franky; Samsonek, Jiří; Knoop, Jan; Egelkraut-Holtus, Marion; Ortlieb, Markus (Food additives & contaminants. Part A, Chemistry, analysis, control, exposure & risk assessment, 2015)
In order to confirm the possibility that recycled fractions from the waste electrical and electronic equipment (WEEE) stream were illegally entering the European market in black polymeric food-contact articles (FCAs), bromine quantification, brominated flame retardant (BFR) identification combined with WEEE-relevant elemental analysis and polymer impurity analysis were performed. From the 10 selected FCAs, seven samples contained a bromine level ranging from 57 to 5975 mg kg(-)(1), which is lower than expected to achieve flame retardancy. The BFRs that were present were tetrabromobisphenol A (TBBPA), decabromodiphenylether (decaBDE), decabromodiphenylethane (DBDPE) and 1,2-bis(2,4,6-tribromophenoxy)ethane (BTBPE). Typical elements used in electronic equipment and present in WEEE were detected either at trace level or at elevated concentrations. In all cases when bromine was detected at higher concentrations, concurrently antimony was also detected, which confirms the synergetic use of antimony in combination with BFRs. This study describes also the measurement of rare earth elements where combinations of cerium, dysprosium, lanthanum, neodymium, praseodymium and yttrium were detected in four of the seven BFR-positive samples. Additionally, polymer purity was investigated where in all cases foreign polymer fractions were detected. Despite the fact that this study was carried out on a very small amount of samples, there is a significant likelihood that WEEE has been used for the production of FCAs.
Keywords: waste electric and electronic equipment; pyrolysis mass spectrometry; brominated flame retardants; Antimony; halogenované difenylethery; food-contact materials; retardanty hoření; polymer recycling; obaly potravin; Polybrominated Biphenyls; Halogenated Diphenyl Ethers; Recycling; Flame Retardants; antimon; Bromine; brom; Europe; Food Packaging; polybrombifenylové sloučeniny; inductively coupled plasma optical emission spectroscopy; plasma spectroscopy; polymery; Polymers; recyklace; brombenzeny; elektronický odpad; waste management; attenuated total reflectance Fourier transformed infrared spectroscopy; X-ray fluorescence; thermal desorption; rare earth elements; Evropa; Electronic Waste; Bromobenzenes